IMPROVING MATERIALS ON READING COMPREHENSION - Merlin Helentina Napitupulu (Jurnal Mantik Penusa, 2018)
The results in this research show that the use of authentic materials is effective to improve the students’ reading comprehension. The use of these materials is effective when they were used together with authentic tasks which provide communicative activities. After the actions were implemented, the students showed some improvements. They could focus on the lesson and actively participated in the teaching and learning process. They got familiar with some reading strategies and could apply them. They were able to scan the detail information of the texts, deduce the meaning of unfamiliar words and understand information when not explicitly stated. They had more interest and motivation in reading. All the various activities made the class atmosphere enjoyable. Key Words: Reading comprehension, authentic material